Data Driven Decision-Making (DDDM) For Business Leaders post COVID-19 Outbreak: A COSTA-webQDA Technique Proposition - Costa, King (My University, 2021)
Business leaders with aptitude for using data intelligibly will be able to perform better post COVID-19 outbreak era (McAfee & Brynjolfsson, 2012). Businesses can no longer ignore the role data plays in making crucial decisions about the next major step to be taken, particularly during the time of disaster or facing potential threats resulting from COVID-19 or similar occurrences. Data informed decision-making will be beneficial to leaders who need to be at the vanguard of knowledge generation within the realm of ideation. COSTA Technique on the webQDA software provides organisations with cutting-edge technology using mix-media applications and web-based strategies to keep up with current trends, insights and muti-perspectival stakeholder analysis in real-time with high levels of efficiency and integrity. This paper presents ideas adapted to the capabilities framework developed by Jia, Hall and Song (2015), addressing five key dimensions in decision-making, such as data governance, data analytics, insights exploitation, performance management and data integration. Using the COSTA Model technique with webQDA, we present how large volumes of textual data, also known and referred to as “big qualitative data” may be transformed to structured, coherent, meaningful and timely decision-making enablers.
Keywords: Big data; Big qual; Business Leaders; COSTA Technique; DDDM; Decision-making; webQDA